The politics of purity : Harvey Washington Wiley and the origins of Federal food policy - Coppin, Clayton A.; High, Jack C. (The University of Michigan Press, 1999)
Reveals how the Pure Food and Drugs Act was influenced by competition among government bureaus and commercial interests.